(untitled) (ELang | An English Language Education Journal, 2016)
This research is a quantitative inquiry. The aim of the research is to know how electronic storybook effective improves students’ pronunciation mastery to the second grade of SMP Al-Mukarramah Bandung and to know the students’ responses towards the use of electronic storybook as a media in improving students’ pronunciation mastery. The research was conducted in Al Mukarramah junior high school to the eight grader students. This research was classed as experimental research which was conducted in six meetings. The sample group of the research was 40 students of eight grader. The data gained from questionnaire, pre test and post test. iStorybook was used as teaching media. The result of this research showed that iStorybook is effective in improving students’ pronunciation mastery in reading narrative text. It was shown by the result of the computation of t obtained (to) was significantly higher that t table (t-table) = 15.079 > 2.021. Meanwhile the result of questionnaire showed positive responses of the respondents. Istorybook has positive effect to teach pronunciation and narrative text. Almost of all the students like studying by using iStorybook (87.5%), they feel iStorybook make them easier to understand, and almost of all the students also feel motivated to learn (82.5%). Based on the result of the research, iStorybook could be considered as effective teaching media. iStorybook could be an interactive teaching media which easy to implement.